HUMAN CAPITAL AS A STRATEGIC RESOURCE FOR SUSTAINABLE DEVELOPMENT: THE CASE OF UZBEKISTAN (Scientific electronic journal "Labor Economics and Human Capital", 2025)
The article explores the theoretical and practical aspects of human capital development in the context of an innovative economy. Key factors influencing its formation – education, healthcare, digitalization, and demographics – are analyzed. Special attention is given to challenges related to the need for lifelong learning and digital transformation. Based on the analysis of the situation in Uzbekistan and international experience, the article offers recommendations for improving the education system, supporting innovation, and developing digital skills to ensure sustainable economic growth.
Keywords: human capital, sustainable development, innovative economy, education, digitalization, skills, healthcare.